Digital Printing with Malay Ornaments with Tallow Gourd Floral Motifs, Jasmine Flower Motifs and Woodland Flower Motifs - Saharja, Komda; Nadeak, Salam Irianto; Telaumbanua, Faudunasoki; Suhendra, Suhendra; Sudirman, Sudirman; Lase, Dewantoro (International Conference on Sciences Development and Technology, 2021)
The themes of conventional Malay adornments typically come from normal themes, to be specific from verdure, fauna, and different materials. Individuals are beginning to focus on culture again by making items with new themes that smell of customary nationality and utilizing advanced printing methods. Furthermore, what has not been investigated further in advanced printing is the fat gourd botanical Motif, the Jasmine blossom, and the Forest Flower theme. There are 3 points of this review, to be specific: To handle the Malay adornment information with the fat gourd botanical themes, the Jasmine bloom themes, and the forest blossom themes into new developments of the fat gourd botanical example, the Jasmine bloom design and the forest blossom themes to contemporary themes, To apply the theme to sheet changes. Prepared to-wear clothing materials produced using an advanced printing process. The strategy in this review includes 3 factors, specifically: Malay theme trimmings, shadings, and plan components of theme decorations. The examination plan in a few phases: plan investigation, design board, investigation, and plan to make style items. The aftereffects of the new theme applied to a style item plan. The plan of these style items applied to digital printing methods, which are current computerized strategies that can print advanced outcomes the themes completed. It's applied to some prepared-to-wear apparel, for example, T-shirts.